2005
DOI: 10.3168/jds.s0022-0302(05)72918-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Dry Periods and Varying Prepartum Diets Alter Postpartum Ovulation and Reproductive Measures

Abstract: There has been substantial recent interest in shortening dry periods; however, the effects of this management change on reproduction have not been adequately evaluated. Holstein cows (n = 58) were assigned in a randomized block design to 1 of 3 treatments: 1) traditional (T) dry period (approximately 56 d) in which cows were fed a low energy diet from 56 to 29 d prepartum followed by a moderate energy diet for 28 d; 2) shortened (S) dry period (approximately 28 d) in which cows were fed continuously a high ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
133
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(148 citation statements)
references
References 47 publications
12
133
2
1
Order By: Relevance
“…1) [24] and potential for enhancing reproductive performance is increased. Some of the same benefits may be obtained by shortening the dry period, however, they will likely be of a smaller magnitude than obtained when eliminating the dry period completely [6].…”
Section: Management Of Dry Period Lengthmentioning
confidence: 95%
See 2 more Smart Citations
“…1) [24] and potential for enhancing reproductive performance is increased. Some of the same benefits may be obtained by shortening the dry period, however, they will likely be of a smaller magnitude than obtained when eliminating the dry period completely [6].…”
Section: Management Of Dry Period Lengthmentioning
confidence: 95%
“…For our first study [6,24], cows were assigned to treatments at -56 d prepartum. The 3 treatments were 1) 56 d dry: cows fed a lowenergy far off diet from -56 to -29 d prepartum and a moderateenergy transition diet from -28 d to parturition; 2) 28 d dry: cows fed lactation diet throughout the dry period; and 3) 0 d dry: cows fed lactation diet until calving.…”
Section: Management Of Dry Period Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…However due to the limited number of animals per treatment, it is difficult to come to a definitive conclusion about the benefits of the M diet in the dry period to fertility variables. Gümen et al (2005) reported improved reproductive measures (time of the first ovulation, first-service conception rate, days open) in groups fed continuously with a high-energy diet and no planned dry period, compared to the traditional two-phase dry period. Colazo et al (2009) in spite of increasing the postpartum dry matter intake and a reduction of negative energy balance, demonstrated that restricted nutrition in the last 4 weeks of gestation negatively affected pregnancy at first insemination.…”
Section: Discussionmentioning
confidence: 99%
“…Although delayed first ovulation is clearly related to body condition score at calving and energy balance of early lactation, it is not as clearly related to milk production. Depending on the experiment but not on herd yield, greater Review: nutritional sub-fertility in the dairy cow milk yield increased the delay to first ovulation and/or to the day of commencement of luteal activity (C-LA) (Petersson et al, 2006), decreased it (Fonseca et al, 1983;Garbarino et al, 2004) or had no effect (Staples et al, 1990;Darwash et al, 1997;Gumen et al, 2005;Lopez et al, 2005;Pedernera et al, 2008). The effect of milk yield may also be approached by breed differences.…”
Section: Milk Production and Reproductive Performancementioning
confidence: 99%